Isospectral integrability analysis of dynamical systems on discrete manifolds - Denis Blackmore; Anatoliy K. Prykarpatsky; Yarema A. Prykarpatsky (Opuscula Mathematica, 2012)
It is shown how functional-analytic gradient-holonomic structures can be used for an isospectral integrability analysis of nonlinear dynamical systems on discrete manifolds. The approach developed is applied to obtain detailed proofs of the integrability of the discrete nonlinear Schrödinger, Ragnisco-Tu and Riemann-Burgers dynamical systems.